CDK8 is associated with RAP2.6 and SnRK2.6 and positively modulates abscisic acid signaling and drought response in Arabidopsis. Issue 5 (2nd August 2020) - Zhu, Yingfang; Huang, Pengcheng; Guo, Pengcheng; Chong, Leelyn; Yu, Gaobo; Sun, Xiaoli; Hu, Tao; Li, Yuan; Hsu, Chuan‐Chih; Tang, Kai; Zhou, Yun; Zhao, Chunzhao; et al.
Summary: CDK8 is a key subunit of Mediator complex, a large multiprotein complex that is a fundamental part of the conserved eukaryotic transcriptional machinery. However, the biological functions of CDK8 in plant abiotic stress responses remain largely unexplored. Here, we demonstrated CDK8 as a critical regulator in the abscisic acid (ABA) signaling and drought response pathways in Arabidopsis . Compared to wild‐type, cdk8 mutants showed reduced sensitivity to ABA, impaired stomatal apertures and hypersensitivity to drought stress. Transcriptomic and chromatin immunoprecipitation analysis revealed that CDK8 positively regulates the transcription of several ABA‐responsive genes, probably through promoting the recruitment of RNA polymerase II to their promoters. We discovered that both CDK8 and SnRK2.6 interact physically with an ERF/AP2 transcription factor RAP2.6, which can directly bind to the promoters of RD29A and COLD‐REGULATED 15A ( COR15A ) with GCC or DRE elements, thereby promoting their expression. Importantly, we also showed that CDK8 is essential for the ABA‐induced expression of RAP2 . 6 and RAP2 . 6 ‐mediated upregulation of ABA‐responsive genes, indicating that CDK8 could link the SnRK2.6‐mediated ABA signaling to RNA polymerase II to promote immediate transcriptional response to ABA and drought signals. Overall, our data provide new insights into the roles of CDK8 in modulating ABA signaling and drought responses.